Comparison of Sanctions for the Crime of Persecution According to the Kerinci Customary Criminal Law and the Indonesian Criminal Law - Ade Saptomo; Nana Lukmana; Riza Endriyana; I Gede Sumerta; Kristofel Aditiya Prathama Pardamean Hutauruk (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This research discusses the application of Kerinci customary criminal law to criminal acts of abuse and its comparison with national criminal law in Indonesia. There is a conflict between Article 351 paragraph (3) of the Criminal Code and the practice of resolving customary abuse in Kerinci Regency. The research method used is normative legal research with a conceptual and analytical approach. The research results show differences in the application of customary and national crimes, with an emphasis on the principle of deliberation in Kerinci customary law. The application of Kerinci's customary crime involves three levels of sanctions, adjusted to the level of the violation, with a Restorative Justice approach. Differences arise in the resolution of minor criminal cases, where customary law involves traditional judges, ninik mamak, and traditional leaders. Harmonization between customary law and national law is crucial to achieving holistic justice.